Виртуалды кеңістікте зорлық-зомбылық көрген балаларға келтірілген зиянды өтеу туралы - Omarova А.Б.; Mukasheva А.А.; Malikova Ш.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The object of research in this article is the legal aspects of compensation for harm caused to children who have been subjected to violence in the virtual space. The development of information and communication technologies has led to the emergence of new types of violence, such as cyberbullying, online harassment and child pornographic content. In this regard, the motivation of the study is the need to analyze compensation for harm as a way to protect the rights of children who have suffered from violence in the online environment. The authors used methods for analyzing research data conducted in the field of law, psychology and information technology, reviewed existing legislative measures and international standards regulating this problem, and also analyzed the effectiveness of legal mechanisms for protecting children from virtual violence. Recommendations are offered to improve the protection of the rights of children subjected to violence in the virtual space. The article was prepared under the project IRN BR 27882414 “Program for the support and rehabilitation of child victims of violence: practical implementation of a network of modular resource centers.” The presented results are important for solving the problem of compensation for harm to children subjected to violence in the virtual space. They can be used to create rehabilitation and assistance programs for children who have suffered from online violence and for further research into the problem.